Inhibin A as a tumor marker for primary bilateral macronodular adrenal hyperplasia. (29th April 2020) - Wurth, Rachel; Kamilaris, Crystal; Nilubol, Naris; Sadowski, Samira M; Berthon, Annabel; Quezado, Martha M; Faucz, Fabio R; Stratakis, Constantine A; Hannah-Shmouni, Fady
Abstract : Summary: Primary bilateral macronodular adrenal hyperplasia (PBMAH) is a rare cause of ACTH-independent Cushing syndrome (CS). This condition is characterized by glucocorticoid and/or mineralocorticoid excess, and is commonly regulated by aberrant G-protein coupled receptor expression may be subclinical, allowing the disease to progress for years undetected. Inhibin A is a glycoprotein hormone and tumor marker produced by certain endocrine glands including the adrenal cortex, which has not been previously investigated as a potential tumor marker for PBMAH. In the present report, serum inhibin A levels were evaluated in three patients with PBMAH before and after adrenalectomy. In all cases, serum inhibin A was elevated preoperatively and subsequently fell within the normal range after adrenalectomy. Additionally, adrenal tissues stained positive for inhibin A. We conclude that serum inhibin A levels may be a potential tumor marker for PBMAH. Learning points: PBMAH is a rare cause of CS. PBMAH may have an insidious presentation, allowing the disease to progress for years prior to diagnosis. Inhibin A is a heterodimeric glycoprotein hormone expressed in the gonads and adrenal cortex. Inhibin A serum concentrations are elevated in some patients with PBMAH, suggesting the potential use of this hormone as a tumor marker. Further exploration of serum inhibin A concentration, as it relates to PBMAH disease progression, is warranted to determine if this hormone could serve as an early detection marker and/or predictor of successful surgical treatment.